Rapid depressurization of a CO2 pipeline – an experimental study. (October 2015) - Vree, Barry; Ahmad, Mohammad; Buit, Luuk; Florisson, Onno
Highlights: Release experiments with nearly pure CO2 were performed with a coil shaped 30 m, 2" tube. Objective was to study pressure, temperature and mass during depressurization. Lower release with 12 mm nozzle resulted in −31.6 °C inside the tube. Tube insulation has no significant impact on pressure-temperature development. Upper release resulted in very low temperatures (−74.0 °C) and solid CO2 formation. Abstract: During transient operation or when a pipeline is punctured or ruptured, a rapid drop in pressure might occur. The depressurization rate depends on the ratio of the mass outflow rate to the mass of CO2 inside the depressurizing pipeline. Rapid depressurization may jeopardize pipeline integrity as very low temperatures may be reached, resulting in brittle pipeline material. An experimental investigation has been carried out to study fast depressurization of a high pressure liquid CO2 pipeline to determine the level of low temperatures reached during this process. A test setup, made up of a coil shaped, 30 m, 2" stainless steel tube with a height of 1.30 m, was constructed. The lower side of the tube was fitted with a 3, 6 and 12 mm nozzle to carry out depressurization experiments with different depressurization rates from an initial pressure of approximately 120 bar. The lowest temperature reached in the tube in this series of experiments was −31.6 °C for the 12 mm nozzle release test. Another test was conducted with the tube fitted with insulation to reduce heat transfer, but no significant impact on the pressure-temperature development was recorded. One last release test was conducted from the upper side of the setup resulting in a longer depressurization time, solid CO2 formation and lower temperatures in the tube (−74 °C).